Lemierre’s Syndrome: Recognising a Typical Presentation of a Rare Condition - James A. Coultas; Neena Bodasing; Paul Horrocks; Anthony Cadwgan (Case Reports in Infectious Diseases)
Lemierre’s syndrome is a rare complication following an acute oropharyngeal infection. The aetiological agent is typically anaerobic bacteria of the genus Fusobacterium. The syndrome is characterised by a primary oropharyngeal infection followed by metastatic spread and suppurative thrombophlebitis of the internal jugular vein. If left untreated, Lemierre’s syndrome carries a mortality rate of over 90%. Whilst relatively common in the preantibiotic era, the number of cases of Lemierre’s syndrome subsequently declined with the introduction of antibiotics. With the increase of antibiotic resistance and a greater reluctance to prescribe antibiotics for minor conditions such as tonsillitis, there are now concerns developing about the reemergence of the condition. This increasing prevalence in the face of an unfamiliarity of clinicians with the classical features of this “forgotten disease” may result in the misdiagnosis or delay in diagnosis of this potentially fatal illness. This case report illustrates the delay in diagnosis of probable Lemierre’s syndrome in a 17-year-old female, its diagnosis, and successful treatment which included the use of anticoagulation therapy. Whilst there was a positive outcome, the case highlights the need for a suspicion of this rare condition when presented with distinctive signs and symptoms.